Comparison between active (pumped) and passive (diffusive) sampling methods for formaldehyde in pathology and histology laboratories. Issue 1 (2nd January 2017) - Lee, Eun Gyung; Magrm, Rana; Kusti, Mohannad; Kashon, Michael L.; Guffey, Steven; Costas, Michelle M.; Boykin, Carie J.; Harper, Martin
ABSTRACT: This study was to determine occupational exposures to formaldehyde and to compare concentrations of formaldehyde obtained by active and passive sampling methods. In one pathology and one histology laboratories, exposure measurements were collected with sets of active air samplers (Supelco LpDNPH tubes) and passive badges (ChemDisk Aldehyde Monitor 571). Sixty-six sample pairs (49 personal and 17 area) were collected and analyzed by NIOSH NMAM 2016 for active samples and OSHA Method 1007 (using the manufacturer's updated uptake rate) for passive samples. All active and passive 8-hr time-weighted average (TWA) measurements showed compliance with the OSHA permissible exposure limit (PEL-0.75 ppm) except for one passive measurement, whereas 78% for the active and 88% for the passive samples exceeded the NIOSH recommended exposure limit (REL-0.016 ppm). Overall, 73% of the passive samples showed higher concentrations than the active samples and a statistical test indicated disagreement between two methods for all data and for data without outliers. The OSHA Method cautions that passive samplers should not be used for sampling situations involving formalin solutions because of low concentration estimates in the presence of reaction products of formaldehyde and methanol (a formalin additive). However, this situation was not observed, perhaps because the formalin solutions used in these laboratories included much less methanol (3%) than those tested in the OSHA Method (up to 15%). The passive samplers in general overestimated concentrations compared to the active method, which is prudent for demonstrating compliance with an occupational exposure limit, but occasional large differences may be a result of collecting aerosolized droplets or splashes on the face of the samplers. In the situations examined in this study the passive sampler generally produces higher results than the active sampler so that a body of results from passive samplers demonstrating compliance with the OSHA PEL would be a valid conclusion. However, individual passive samples can show lower results than a paired active sampler so that a single result should be treated with caution.